Yoga en la Escuela. An experience in the city of Rosario (Praxis Educativa, 2020)
Yoga is a comprehensive discipline that promotes states of balance and well-being through a set oflifestyle guidelines and techniques. In view of the extensive research showing the benefits of the inclusionof yoga in educational settings, in 2018 we launched a project entitled “Yoga en la Escuela” (“Yoga at School”) in a secondary school in the city of Rosario, with highly positive results in terms of students’comprehensive learning. The inclusion of weekly classes taught to the first year class and the training ofsome of the teachers in breathing and concentration techniques have had a positive impact on emotionaldevelopment, personalwell-being and academic performance, both as perceived by the studentsthemselves and by their families and teachers.
Keywords: yoga; education; health; emotions; well-being